2005
DOI: 10.1002/ejoc.200500156
|View full text |Cite
|
Sign up to set email alerts
|

Pyridone Dipeptides – Synthesis of a Novel Peptide Chromophore

Abstract: Sequential elimination of two water molecules transfers the diols 2 and 3 into the pyridone dipeptide 1. Both dehydration steps become part of the peptide synthesis under appropriate reaction conditions. A straightforward strategy for the incorporation of 1 in oligopeptide sequences is presented here. As part of the oligopeptide backbone, 1 has a local rigidifying effect which was studied in the cyclic octapeptides 16 and 25. Both cyclopeptides exhibit conformational averaging although a fixed conformation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The title compound, (I), was prepared by oxidation of methyl (3R)-6-tert-butoxycarbonylamino-5-oxo-2,3-dihydro-5H-1,3-thiazolo[3,2-a]pyridine-3-carboxylate, which can easily be synthesized, starting from l-cysteine methylester hydrochloride and d--glucuronolactone, finally followed by elimination of two molecules of water (Tremmel et al, 2003;Tremmel & Geyer, 2005). In order to investigate the influence of the sulfur on the fluorescence properties of this compound, it was oxidized using m-CPBA to yield the two possible diastereomeric sulfoxides and the corresponding sulfone.…”
Section: Commentmentioning
confidence: 99%
“…The title compound, (I), was prepared by oxidation of methyl (3R)-6-tert-butoxycarbonylamino-5-oxo-2,3-dihydro-5H-1,3-thiazolo[3,2-a]pyridine-3-carboxylate, which can easily be synthesized, starting from l-cysteine methylester hydrochloride and d--glucuronolactone, finally followed by elimination of two molecules of water (Tremmel et al, 2003;Tremmel & Geyer, 2005). In order to investigate the influence of the sulfur on the fluorescence properties of this compound, it was oxidized using m-CPBA to yield the two possible diastereomeric sulfoxides and the corresponding sulfone.…”
Section: Commentmentioning
confidence: 99%
“…The title compound, (I), was prepared in a few steps, starting with the condensation of d-aldurono-2,5-lactone and l-cysteine methyl ester hydrochloride, followed by the elimination of two molecules of water (Tremmel et al, 2003;Tremmel & Geyer, 2005). The antiparallel orientation of the two molecules of the asymmetric unit represents a mini-sheet with two antiparallel intermolecular hydrogen bonds.…”
Section: Commentmentioning
confidence: 99%
“…It was already shown that such a dehydration can be provoked during peptide synthesis without requiring extra synthetic transformations (route b in Scheme 1). 5 Yet, for the several-fold introduction of this bicyclic 2-pyridone into a 36mer neuropeptide (Biochemistry Leipzig, A. Beck-Sickinger) we were urged to develop a building block which is amenable for solid-phase peptide synthesis (route a in Scheme 1). The following protocol is more efficient than the original procedure and additionally allows the desired side-chain diversification.…”
mentioning
confidence: 99%